Recent Advances in Electrochemical Oxidative Cross-Coupling for the Construction of C–S Bonds - Song, Chunlan; Liu, Kun; Dong, Xin; Chiang, Chien-Wei; Lei, Aiwen (Synlett, 2019)
With the importance of sulfur-containing organic molecules, developing methodologies toward C–S bond formation is a long-standing goal, and, to date, considerable progress has been made in this area. Recent electrochemical oxidative cross-coupling reactions for C–S bond formation allow the synthesis of sulfur-containing molecules from more effective synthetic routes with high atom economy under mild conditions. In this review, we highlight the vital progress in this novel research arena with an emphasis on the synthetic and mechanistic aspects of the organic electrochemistry reactions.1 Introduction2 Electrochemical Oxidative Sulfonylation for the Formation of C–S Bonds2.1 Applications of Sulfinic Acid Derivatives for the Formation of C–S Bonds2.2 Applications of Sulfonylhydrazide Derivatives for the Formation of C–S Bonds3 Electrochemical Oxidative Thiolation for the Formation of C–S Bonds3.1 Applications of Disulfide Derivatives for the Formation of C–S Bonds3.2 Applications of Thiophenol Derivatives for the Formation of C–S Bonds4 Electrochemical Oxidative Thiocyanation for the Formation of C–S Bonds5 Electrochemical Oxidative Cyclization for the Formation of C–S Bonds6 Conclusion
Keywords: electrochemistry; C–S bond formation; sulfonylation; thiolation; thiocyanation; cyclization